The limits of hegemony: U.S. banks and Chilean firms in the Cold War - Felipe Aldunate; Felipe González; Mounu Prem (Queen Mary University of London, School of Economics and Finance, 2023)
Governments in hegemonic states use economic sanctions to induce changes in other countries. What happens to international business networks when these sanctions are in place? We use new historical firm-level data to document the destruction of financial relations between U.S. banks and Chilean firms after socialist Salvador Allende took office in 1970. Business reports and stock prices suggest that firms were mostly unaffected by having fewer links with U.S. banks. Substitution of financial relations towards domestic banks appears to be the key mechanism explaining these findings.
Keywords: 330; firms; banks; Cold War; United States; Salvador Allende